Dose enhancement by bismuth oxide nanoparticles for HDR brachytherapy. (March 2020) - Sisin, N N T; Azam, N A; Rashid, R A; Abdullah, R; Razak, K A; Abidin, S Z; Rahman, W N
Abstract: Escalation of biological damage through the induction of dose enhancement effect in radiotherapy cancer treatment by high-Z nanoparticles (NPs) has recently been the subject of growing interest. Hence, this study was conducted primarily to investigate the enhancement of brachytherapy (source Ir 192 ) efficacy by bismuth oxide nanoparticles (BiONPs) on cervical cancer cells. Radiosensitization effect was tested against different size and concentration of BiONPs. After irradiation with radiation doses ranging from 0 to 4 Gy, the survival of the cell was quantified by clonogenic assay and presented in survival curves fitted using the LQ model. Dose enhancement (DE) factor was extrapolated from the curve at 50% of cell survival and calculated. The results marked out the dependency of DE on nanoparticles size and concentrations. The optimum size of BiONPs was found to be 80 nm with a concentration of 0.00025 mM, in which the DEF is 1.88. In conclusion, this study suggests that the induction of the DE effect is dependent on the size and concentration of the nanoparticles.